Contemporary management of rectal injuries at Level I trauma centers: The results of an American Association for the Surgery of Trauma multi-institutional study. Issue 2 (February 2018) - Brown, Carlos V.R.; Teixeira, Pedro G.; Furay, Elisa; Sharpe, John P.; Musonza, Tashinga; Holcomb, John; Bui, Eric; Bruns, Brandon; Hopper, H. Andrew; Truitt, Michael S.; Burlew, Clay C.; Schellenberg, Morgan; et al.
Abstract : INTRODUCTION: Rectal injuries have been historically treated with a combination of modalities including direct repair, resection, proximal diversion, presacral drainage, and distal rectal washout. We hypothesized that intraperitoneal rectal injuries may be selectively managed without diversion and the addition of distal rectal washout and presacral drainage in the management of extraperitoneal injuries are not beneficial. METHODS: This is an American Association for the Surgery of Trauma multi-institutional retrospective study from 2004 to 2015 of all patients who sustained a traumatic rectal injury and were admitted to one of the 22 participating centers. Demographics, mechanism, location and grade of injury, and management of rectal injury were collected. The primary outcome was abdominal complications (abdominal abscess, pelvic abscess, and fascial dehiscence). RESULTS: After exclusions, there were 785 patients in the cohort. Rectal injuries were intraperitoneal in 32%, extraperitoneal in 58%, both in 9%, and not documented in 1%. Rectal injury severity included the following grades I, 28%; II, 41%; III, 13%; IV, 12%; and V, 5%. Patients with intraperitoneal injury managed with a proximal diversion developed more abdominal complications (22% vs 10%, p = 0.003). Among patients with extraperitoneal injuries, there were more abdominal complications in patients who received proximal diversion ( p = 0.0002), presacral drain ( p = 0.004), or distal rectal washout ( p = 0.002). After multivariate analysis, distal rectal washout [3.4 (1.4–8.5), p = 0.008] and presacral drain [2.6 (1.1–6.1), p = 0.02] were independent risk factors to develop abdominal complications. CONCLUSION: Most patients with intraperitoneal injuries undergo direct repair or resection as well as diversion, although diversion is not associated with improved outcomes. While 20% of patients with extraperitoneal injuries still receive a presacral drain and/or distal rectal washout, these additional maneuvers are independently associated with a three-fold increase in abdominal complications and should not be included in the treatment of extraperitoneal rectal injuries. LEVEL OF EVIDENCE: Therapeutic study, level III.